Pharmacy practice in Developing Countries : achievements and challenges - Fathelrahman, Ahmed; Ibrahim, Mohamed Izham; Wertheimer, Albert (London : Elsevier, 2016)
Pharmacy Practice in Developing Countries: Achievements and Challenges offers a detailed review of the history and development of pharmacy practice in developing countries across Africa, Asia, and South America. Pharmacy practice varies substantially from country to country due to variations in needs and expectations, culture, challenges, policy, regulations, available resources, and other factors. This book focuses on each country's strengths and achievements, as well as areas of weakness, barriers to improvement and challenges. It sets out to establish a baseline for best practices, taking all of these factors into account and offering solutions and opportunities for the future. This book is a valuable resource for academics, researchers, practicing pharmacists, policy makers, and students involved in pharmacy practice worldwide as it provides lessons learned on a global scale and seeks to advance the pharmacy profession.
9. Achievements of pharmacy practice9.1 Advancing roles of hospital pharmacists; 9.2 Expanding roles of pharmacists in community settings; 9.3 System changes facilitating the advancement of pharmacy practice; 10. Challenges; 11. Recommendations and way forward; 12. Lessons learned; 13. Points to remember; Acknowledgments; References; 2 -- Pharmacy Practice in Malaysia; 1. Introduction; 1.1 Background of Malaysia healthcare system; 2. Health sector and system; 3. Vital health statistics; 4. Medicines use issues; 5. Pharmacy practice in Malaysia.
Off-Campus Access: Athens ID and Password Required
On-Campus Access: No User ID or Password Required
Includes index.
Mode of access: Internet
Keywords: Pharmacy -- Practice -- Developing countries; Developing Countries; Pharmacy; MEDICAL -- Pharmacology; Pharmacy -- Practice; Developing countries; Electronic books